Análisis del aprendizaje y enseñanza sobre tradiciones artísticas y saberes científicos de grupos étnicos colombianos por parte de los estudiantes del curso 902, jornada mañana de la institución Gabriel Betancourt Mejía en Bogotá. (2022)
This research monograph of investigation seeks to identify what knowledges is faced with artistic traditions and scientific knowledge within the framework of education with multiethnic and multicultural content possessed by ninth grade students (902) of the Gabriel Betancourt Mejía school, public formal education institution of Bogotá. For the resolution of the objective sets, the opinions of the students and teachers of the ninth grade were taken into account. Being fundamental to the research. With this in mind, a series of questions expressed in questionnaire and interviews were developed, that allowed the collections of information and relevant data on the teachings shared in the school and the content that points to the construction of an education that considers the Colombian reality and its characteristic population groups relevant. This paved the way for determining what was taught and what was learned about ethnic groups, taking into account aspects of their artistic traditions and scientific knowledge that were shared with students during the period of 2021 as part of the global Covid-19 pandemic and virtual education.